Social class and suicidal behaviour: the associations between social class and the characteristics of deliberate self-harm patients and the treatment they are offered. - Hawton, K; Harriss, L; Simkin, S; Bale, E; Bond, A (2001)
BACKGROUND: Rates of deliberate self-harm (DSH) in the United Kingdom are much higher in lower than upper social class groups. Previous investigations have shown differences in socio-demographic and clinical characteristics of male patients according to social class. In two studies of DSH patients in Edinburgh the extent of provision of psychiatric aftercare was inversely related to social class. These findings have not been investigated in other areas. METHOD: Data collected through the Oxford Monitoring System for Attempted Suicide were used to examine the association between social class and socio-demographic and clinical characteristics in male and female DSH patients who presented to the general hospital in Oxford between mid-1988 and 1996 and to determine whether the previously reported social class differences in provision of psychiatric aftercare were replicated. RESULTS: Data on social class were available for 2,828 DSH patients (1,290 males, 1,538 females). In both genders, lower social class group tended to be associated with younger age. In males, the main social class differences were found in under-35-year-olds, in whom lower social class was related to criminal record, violence to others and drug misuse. In females, psychiatric disorders were diagnosed more frequently in the higher social class groups, but only in the under-35 age group. In neither gender was there a significant association between social class and the frequency of offer of psychiatric aftercare following DSH. CONCLUSIONS: There are considerable variations in socio-demographic and clinical characteristics of both male and female DSH patients in different social classes, especially in younger patients. The reason for the absence of a marked social class gradient in psychiatric aftercare found in this study in contrast to the results from previous investigations may be related to differences in styles of service.